IMPROVING THE SPEAKING SKILLS OF PRIMARY SCHOOL STUDENTS THROUGH A COMMUNICATIVE APPROACH - Imro Atus Soliha; Agustiarini Eka Dheasari (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The purpose of this study is to find out the extent to which the communicative approach is able to have an appropriate influence on the speaking skills of elementary school students. The method used in this research is action research. This research was conducted at SD Negeri Tonga, The research subject was class V- A students totaling 24 students consisting of 11 boys and 13 girls. The participants involved in this study were the researchers themselves who acted as teachers who taught in class V-A and class V-B teachers as collaborators. The instrument used in this study was an observation sheet. Based on the results of data processing and analysis, the conclusion of the results of this study is that there is a significant improvement in speaking skills through a communicative approach in grade V students with theme one "Objects in the Environment," subtheme "Humans and the Environment". In cycle I, 13 students (54.17%) were complete, and 11 students (45.83%) were not complete. In cycle II theme two "Events in Life", subtheme "Various Events in Life", as many as 18 students (75%) were complete, and 6 students (25%) were not complete with an average score of 80.Keywords:  Speaking Skills; Communicative Approach; Primary School